Validity and intrarater reliability of a novel device for assessing Plantar flexor strength - O´Neill, S.; Weeks, A.; Norgaa; Nørgaard, S. J.; Gronbech Jorgensen, M. (PLOS ONE, 2023)
Introduction Plantar flexor weakness is an identified prospective factor for developing Achilles tendinopathy. Various authors have reported relationships between symptoms and weakness of this muscle group. Despite this relationship, many clinicians and researchers fail to examine Plantar flexor strength due to the cumbersome, stationary and expensive nature of an isokinetic dynamometer (IKD), known as the "Gold Standard". This study examined the validity and reliability of a fast, easy and portable device for assessing plantarflexion. Methods Validity between the Cybex NORM® by Humac and the C-Station by Fysiometer was explored using Pearson correlation coefficient. Participants were randomly selected to start in the Cybex NORM® or the FysioMeter C-Station. Intra-rater reliability on the C-station was investigated by test-retest two days apart using Intraclass Correlation Coefficient (ICC). All testing involved isometric maximal force of the soleus muscle with the knee at 90 degrees flexion. Results 40 healthy university students were recruited for the validity part, while 65 healthy university students were recruited for the reliability part of the study. The mean peak torque on the IKD was 198.55Nm (SD 94.45) versus 1443.88 (412.82)N on the C-Station. The results of the Pearson correlation revealed an r-value of r = 0.72 with a 95%CI 0.52-0.84. The test re-test reliability was calculated as an ICC of 0.91 with a (95%CI 0.86-0.94). Conclusions The C-Station by Fysiometer appears to provide valid measures and have excellent reliability for Plantar flexor isometric strength. It would appear suitable for both clinical and research work.